The Influence of E-Banking Transaction and Fee-Based Income on Bank Profitability (Study in Bank Central Asia) - Awalia, Syavira Gita (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
The purpose of this study was to determine the effect of e-banking transactions and fee-based income on bank profits at Bank Central Asia partially. In this study, two independent variables were tested, namely e-banking transactions and fee-based income and one dependent variable, namely bank profits. This study uses secondary data originating from the official website of the Asian Central Bank with purposive sampling method with the characteristics of issuing annual financial reports from 2013-2020, presenting data or information related to e-banking transactions and fee-based income in their effect on bank profits. The results showed, the first variable test, the e-banking transaction variable, did not have a significant effect on bank. While the second variable, fee-based income, has a positive and significant effect on bank profitability. Keywords: E-Banking Transaction, Fee-Based Income, Bank Profitability.